Perspectiva del Combate a la Pobreza en México a Partir de una Visión Universitaria - Lara López, Arturo; Salgado Gómez, Antonio; Montiel Domínguez, Francisco (Acta Universitaria, 2006)
In global boundaries, poverty is perhaps, the most oppressive affliction world wide. During the last decade, in the last century, one in three children were under nutritional standard conditions, around three million infants died every year of illnesses related to poverty conditions, and one million women died every year due to health problems related to pregnancy complications, more than thousand two hundred million people did not have drinking water supply, and proper living conditions, and thousand million adults world wide did not know how to read and write. In our country, society and government have to do something to fight this social illness that inhibits human integral development, and obstructs any possibility to create and live in a better country for all its inhabitants. Educational conditions in the country are a part of what is known as human resources, and have a fundamental repercussion on general living conditions in the population. The changes derived from educationon human beings are fundamental to the creation and set in motion of programs that fight poverty, through coordinated actions that include students community service, more education and educational services, the involvement of teachers in community development projects in different areas, as well as the participation of researchers in knowledge application projects that tend to improve general living conditions among the population. Society, government and university can set the foundations and build a future Mexico, with vision, and perspective, trust and decision to make our Mexico a more egalitarian, fair and happier country.